Limbu Language in the Touchstone of Honorific - Tumbahang, Mohan Kumar (JODEM: Journal of Language and Literature, 2024)
This article aims to explore the forms of honorific employed in the Limbu language communication. It is primarily based on descriptive design in which non-numerical data have been expounded as well as analyzed. The data have been elicited from consulting the library and the native speakers’ empirical insights. The nature of the study is essentially related to the sociolinguistic theory which attempts to observe the language in relation to the society. The notions of politeness and honorific are directly linked to the sociolinguistic aspect. From the analysis, it is apparent that the forms of honorific exist with at five different degrees/levels ranging from the highest level to the lowest one. In the same way, the Limbu language lacks honorific marking personal pronouns and the corresponding verbs. Grammatically the same verb is used at five different honorific levels. Honorific in Limbu can be achieved through the three distinct manners. This article is helpful for interested individuals to broaden their understanding of the honorific system in the Limbu language. It can be equally insightful to the concerned persons who are focusing their study on sociolinguistic aspect of other Tibeto-Burman languages.